Palladium Nanoparticles Hardwired in Carbon Nanoreactors Enable Continually Increasing Electrocatalytic Activity During the Hydrogen Evolution Reaction. Issue 22 (15th September 2021) - Aygün, Mehtap; Guillen‐Soler, Melanie; Vila‐Fungueiriño, Jose M.; Kurtoglu, Abdullah; Chamberlain, Thomas W.; Khlobystov, Andrei N.; del Carmen Gimenez‐Lopez, Maria
Abstract: Catalysts typically lose effectiveness during operation, with much effort invested in stabilising active metal centres to prolong their functional lifetime for as long as possible. In this study palladium nanoparticles (PdNP) supported inside hollow graphitised carbon nanofibers (GNF), designated as PdNP@GNF, opposed this trend. PdNP@GNF exhibited continuously increasing activity over 30000 reaction cycles when used as an electrocatalyst in the hydrogen evolution reaction (HER). The activity of PdNP@GNF, expressed as the exchange current density, was always higher than activated carbon (Pd/C), and after 10000 cycles PdNP@GNF surpassed the activity of platinum on carbon (Pt/C). The extraordinary durability and self‐improving behaviour of PdNP@GNF was solely related the unique nature of the location of the palladium nanoparticles, that is, at the graphitic step‐edges within the GNF. Transmission electron microscopy imaging combined with spectroscopic analysis revealed an orchestrated series of reactions occurring at the graphitic step‐edges during electrocatalytic cycling, in which some of the curved graphitic surfaces opened up to form a stack of graphene layers bonding directly with Pd atoms through Pd−C bonds. This resulted in the active metal centres becoming effectively hardwired into the electrically conducting nanoreactors (GNF), enabling facile charge transport to/from the catalytic centres resulting in the dramatic self‐improving characteristics of the electrocatalyst. Abstract : Room for self‐improvement : Palladium nanoparticles confined inside hollow graphitised carbon nanofibers exhibit a remarkable increasing activity over 30000 reaction cycles when used as electrocatalyst in the hydrogen evolution reaction, surpassing the activity of platinum on carbon. During operation, palladium becomes hardwired into the graphitic step‐edges that open, enabling facile charge transport to/from the catalytic centres resulting in the dramatic self‐improving characteristics of the electrocatalyst.